Nanecōḍuni kavitā vaibhavamu : Nannecōḍuni padyālaku rucira vyākhyānamu - Vēṅkaṭarāvu, Niḍudavōlu, 1904- (Yuvabhārati pracuraṇa ;, 1976)
Commentary, with text, on selections from Nannecōḍa's Kumārasambhavamu, poem dealing with the marriage of Siva and Parvati and the birth of their son Kumara, Hindu war god.